A boost type switched‐capacitor multi‐level inverter for renewable energy sources with Self‐Voltage balancing of capacitors. (30th April 2021) - Deliri, Saeid; Varesi, Kazem; Siwakoti, Yam P.; Blaabjerg, Frede
Summary: This article proposes a single‐phase double‐source 27‐level basic inverter structure based on Switched‐Capacitors (SCs) circuit for renewable energy sources. The extendibility, low Blocking Voltage (BV) on semiconductors, step‐up capability, and self‐voltage balancing of capacitors are the main advantages of the suggested basic structure. Using double H‐bridges to generate bi‐polar voltage waveform, the blocking voltage on the semiconductors limit to only 0.692 V o, max . The Average of Normalized Blocking Voltage (ANBV) on semiconductors of basic topology is only about 33.52%. Two extended structures have been presented with higher output voltage steps and boosting factors. The first extended topology composed of two (right and left) Generalized Switched Capacitor based Modules (GSCMs), results in reduced sources (only 2), increased steps, low BV on semiconductors, and boosting factor of 2 n ( n : number of SC Cells). The second extended topology can be realized by applying more cascaded Switched‐Capacitor Modules (SCMs), which benefits from quadruple‐gain and increased levels (9 m, m : number of cascaded modules). The suggested topologies properly supply the zero or low power‐factor load types. The superiority of proposed configurations over recently presented similar structures has been compared and verified. The experimental outcomes of the basic topology have also been provided to validate its correct operation. Abstract : This article proposes a single‐phase double‐source 27‐level basic inverter structure based on Switched‐Capacitors (SCs) circuit for renewable energy sources. The main advantages are: High output power quality without requirement to filter High output efficiency Step‐up capability, which is necessary in PV Applications Utilizing simple modulation technique Low blocking voltage on semiconductors, leading to low‐size, low‐cost, and low‐loss switches/diodes Reduced device count and low Cost‐Function Self‐Balanced voltage of capacitors without any controller